Women and flexitime - Abdul Kadir, Adibah; Maulad Bahro, Khadijah; Mohd Rosli, Nur Amalina; Ismail, Fadillah (Penerbit Uthm, 2019)
Trends of working hours now shows that flexible work arrangements that allow employees to have working hours that fluctuate compare to the working hours of eight hours a day, more and more popular with the development of technology such as the internet, video conferencing, and most recently through 'cloud-computing'. At present also, it can be seen that the individual requires more balance between work and life at the same time they have more time to take care of their families. Therefore, they require more independent work arrangements to meet the needs of work and their daily lives. Traditionally working time where the time work began at nine to five job is increasingly not required (Manpower, 2010).